Implementation of Sex Education in Adolescent at SMPN 1 Cikarang Selatan in Fighting Free Association with the Princes Program - Maghfirotul Ghina; Amirudin Amirudin; Acep Nurlaeli (Universitas Muhammadiyah Enrekang, 2023)
The phenomenon that has been happening lately is the number of cases of sex crimes that are dominated by minors. Many things cause children in their teens to practice sexual deviation or free sex as a way of escaping from various problems and the lack of children's ability to control themselves from their emotions. Sex education is an effort to teach, raise awareness and provide information about sexual issues to children and adolescents, since they are familiar with issues related to sexual instincts and marriage, so that when children and adolescents have grown into youths they can understand the affairs of life. , he already knows what is forbidden and what is permitted. Furthermore, he is even able to apply Islamic behavior as a moral and habit of life, and is not enslaved by lust and immersed in a hedonic lifestyle. The women's program is an alternative that is implemented in this school as a prevention of promiscuity. Women's education is the process of educating or teaching that is carried out by education in changing one's character, behavior and personality related to all things women's activities, both young women and adult women. This study uses a qualitative approach. Qualitative research is research that intends to understand phenomena about what is experienced by research subjects, for example behavior, perceptions, motivations, actions, and others holistically, and in a descriptive way in the form of words and discussion, in a natural context with using natural methods. Keywords: Sex education, Adolescents, Women's Program